Indonesia's Foreign Policy on Security, Case Study : South China Sea Dispute - Imaduddin, Muhammad Dzulfiqar Faza; Hadisancoko, Rizerius Eko; Herman, Erry (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia's foreign policy on security, particularly in the South China Sea, is a multifaceted and successful strategy rooted in historical imperatives, geographical considerations, and principled values. This analysis employs a comprehensive methodology, encompassing an examination of Indonesia's historical pursuit of territorial integrity, its strategic geographic positioning, and the influence of core values in shaping foreign policy. By actively participating in regional and international forums, Indonesia employs active diplomacy, adheres to a policy of neutrality, and enforces maritime laws, contributing to conflict resolution and regional stability. Through a detailed analysis of its roles as a mediator, facilitator of maritime cooperation, promoter of international law, and key participant in regional initiatives, this study underscores Indonesia's significant impact on fostering peace and stability in the South China Sea. The examination of Indonesia's success lies in its ability to empower ASEAN, strengthen bilateral relations, and enhance maritime defense capabilities, all of which collectively contribute to the nation's pivotal role as a regional leader in shaping the geopolitical landscape of the South China Sea. Indonesia's foreign policy on security, especially in the South China Sea, emerges as a comprehensive and successful strategy, blending historical awareness, strategic positioning, principled values, and proactive engagement.